KONSEPSIONAL ALI MARKASA DALAM PENCIPTAAN TARI NGREMO JOMBANGAN - Pance Mariati; Nanik Sri Prihatini (Institut Seni Indonesia Surakarta, 2015)
Dance Ngremo Jombangan is one of the dances Ngremo in East Java that has a special characteristiccompared to other dance Ngremo. The dance is created by Ali Markasa, a pengreman (Ngremo dancer) fromJombang. Ali treats the movements in such a way that they are able to bring a technique of an attractive anddynamic movement in dance Ngremo Jombangan. The research aims to convey Ali Markasa’s concept increating dance Ngremo Jombangan. It uses the method of qualitative analysis descriptive with etnokoreologiapproach. The result shows that Ali Markasa wants to create dance Ngremo because of his experience as apengreman in Ludruk performance. He learns that the movement of dance Ngremo is common and spiritless.For the reason, he wants to create a dance Ngremo that is more attractive and dynamic called Dance NgremoJombangan. His creativity in dance ngremo is able to give a special characteristic. It can be seen in themovements of sadukan sampur, tanjak, and ayam alas. His technique of movements is dynamic and attractive.It is often known as njangkrik upo because of his agility in dancing. Keywords: concept, Ali Markasa, dance Ngremo Jombangan